131k views
0 votes
HELP IT'S URGENT.
Please show workings.
No 4 (see image)

HELP IT'S URGENT. Please show workings. No 4 (see image)-example-1
User Drclaw
by
4.9k points

2 Answers

1 vote


\huge \underline{\tt Question} :

If α and β are the roots of the equation ax² + bx + c = 0, where a, b and c are constants such that a ≠ 0, find in terms of a, b and c expressions for :


  1. \tt (1)/(\alpha ^2) + (1)/(\beta ^2)
  2. α³ + β³


\\


\huge \underline{\tt Answer} :


  1. \bf (1)/(\alpha ^2) + (1)/(\beta ^2) = (b^2 - 2ac)/(c^2 )

  2. \bf \alpha ^3 + \beta ^3 = ( - b^3 + 3abc)/(a^3)


\\


\huge \underline{\tt Explanation} :

As, α and β are the roots of the equation ax² + bx + c = 0

We know that :


  • \underline{\boxed{\bf{Sum \: of \: roots = (- coefficient \: of \: x)/(coefficient \: of \: x^2)}}}

  • \underline{\boxed{\bf{Product \: of \: roots = (constant \: term)/(coefficient \: of \: x^2)}}}


\tt : \implies \alpha + \beta = (-b)/(a)

and


\tt : \implies \alpha\beta = (c)/(a)


\\

Now, let's solve given values :


\bf \: \: \: \: 1. \: (1)/(\alpha ^2) + (1)/(\beta ^2)


\tt : \implies (\beta ^2 + \alpha ^2)/(\alpha ^2 \beta ^2)


\tt : \implies (\alpha ^2 + \beta ^2)/(\alpha ^2 \beta ^2)


\\

Now, by using identity :


  • \underline{\boxed{\bf{a^2+ b^2 = (a+b)^2 -2ab}}}


\tt : \implies ((\alpha + \beta)^2 - 2 \alpha\beta)/((\alpha\beta)^2)


\\

Now, by substituting values of :


  • \underline{\boxed{\bf{\alpha + \beta = (-b)/(a)}}}

  • \underline{\boxed{\bf{\alpha\beta = (c)/(a)}}}


\tt : \implies (\Bigg((-b)/(a)\Bigg)^2 - 2 * (c)/(a))/(\Bigg((c)/(a)\Bigg)^2)


\tt : \implies ((b^2)/(a^2) - (2c)/(a))/((c^2)/(a^2))


\tt : \implies ((b^2)/(a^2) - (2ac)/(a^(2) ))/((c^2)/(a^2))


\tt : \implies ((b^2 - 2ac)/(a^2 ))/((c^2)/(a^2))


\tt : \implies \frac{b^2 - 2ac}{\cancel{a^2} } * \frac{ \cancel{a^2}}{c^2}


\tt : \implies (b^2 - 2ac)/(c^2 )


\\


\underline{\bf Hence, \: (1)/(\alpha ^2) + (1)/(\beta ^2) = (b^2 - 2ac)/(c^2 )}


\\


\bf \: \: \: \: 2. \: \alpha ^3 + \beta ^3


\\

By using identity :


  • \underline{\boxed{\bf{a^3+ b^3 = (a+b)(a^2 -ab + b^2)}}}


\tt : \implies (\alpha + \beta)(\alpha ^2 - \alpha\beta + \beta ^2)


\tt : \implies (\alpha + \beta)(\alpha ^2 + \beta ^2 - \alpha\beta)


\\

By using identity :


  • \underline{\boxed{\bf{a^2+ b^2 = (a+b)^2 -2ab}}}


\tt : \implies (\alpha + \beta)(\alpha + \beta)^2 -2 \alpha\beta - \alpha\beta)


\tt : \implies (\alpha + \beta)((\alpha + \beta)^2 -3 \alpha\beta)


\\

Now, by substituting values of :


  • \underline{\boxed{\bf{\alpha + \beta = (-b)/(a)}}}

  • \underline{\boxed{\bf{\alpha\beta = (c)/(a)}}}


\tt : \implies \Bigg((-b)/(a)\Bigg)\Bigg( \bigg((-b)/(a) \bigg)^2 -3 * (c)/(a)\Bigg)


\tt : \implies \Bigg((-b)/(a)\Bigg)\Bigg((b^2)/(a^2) - (3c)/(a)\Bigg)


\tt : \implies \Bigg((-b)/(a)\Bigg)\Bigg((b^2)/(a^2) - (3ac)/(a^(2) )\Bigg)


\tt : \implies \Bigg((-b)/(a)\Bigg)\Bigg((b^2 - 3ac)/(a^2) \Bigg)


\tt : \implies (-b)/(a) * (b^2 - 3ac)/(a^2)


\tt : \implies ( - b(b^2 - 3ac))/(a * a^2)


\tt : \implies ( - b^3 + 3abc)/(a^3)


\\


\underline{\bf Hence, \: \alpha ^3 + \beta ^3 = ( - b^3 + 3abc)/(a^3)}

User Max Hampton
by
4.6k points
2 votes

Answer:

  • (i) (b² - 2ac)/c²
  • (ii) (3abc - b³)/a³

Explanation:

α and β are the roots of the equation:

  • ax² + bx + c = 0

Sum of the roots is:

  • α + b = -b/a

Product of the roots is:

  • αβ = c/a

Solving the following expressions:

(i)

  • 1/α² + 1/β² =
  • (α² + β²) / α²β² =
  • ((α + β)² - 2αβ) / (αβ)² =
  • ((-b/a)² - 2c/a) / (c/a)² =
  • (b²/a² - 2c/a) * a²/c² =
  • b²/c² - 2ac/c² =
  • (b² - 2ac)/c²

----------------

(ii)

  • α³ + β³ =
  • (α + β)(α² - αβ + β²) =
  • (α + β)((α + β)² - 3αβ) =
  • (α + β)³ - 3αβ(α + β) =
  • (-b/a)³ - 3(c/a)(-b/a) =
  • -b³/a³ + 3bc/a²=
  • 3abc/a³ - b³/a³=
  • (3abc - b³)/a³

User Evfwcqcg
by
5.5k points